Perceptions of protective actions for a water contamination emergency. Issue 7 (3rd July 2017) - Lindell, Michael K.; Mumpower, Jeryl L.; Huang, Shih-Kai; Wu, Hao-Che; Samuelson, Charles D.; Wei, Hung-Lung
Abstract : Local authorities who believe their water systems are contaminated need to warn those at risk to take protective actions. In the past, such efforts have often achieved only partial success in preventing people from deciding to continue consumption of contaminated drinking water. To examine the possible antecedents of decisions to comply with water consumption advisories, this study examined 110 Boston residents' actual protective actions and 203 Texas students' expected protective actions; their perceptions of three protective actions on seven attributes; and their risk perceptions, water contamination experience, facilitating conditions, and demographic characteristics. The profiles of the protective actions for the hazard-related and resource-related attributes suggest reasons why people preferred to use bottled water rather than boil or personally chlorinate water. In particular, perceived effectiveness in protecting health was the most important correlate of protective action, which means that a protective action can have a high level of implementation even though it has poor ratings on other attributes such as cost. In addition, this study indicates public health officials may also need to address people's misconceptions about the hazard-related and resource-related attributes of any relevant protective actions. Finally, consistent with an extensive body of previous research, students were similar to residents in many important respects even though were some statistically significant differences.